Pollution incidence and political jurisdiction: evidence from the TRI - Eric Helland; Andrew B. Whitford (Claremont McKenna College, Department of Economics, 2002)
Few issues are more contentious for local communities than industrial pollution. When local industries pollute, lawmakers and regulators must balance two primary concerns: economic prosperity and the environment. The role of political pressure is well-documented in environmental policy. What is less clear is the role jurisdictional or boundary considerations play in determining the implementation of environmental laws. Anecdotal evidence suggests that local regulators are more lenient in their treatment of polluters when the incidence of pollution falls partially on those outside the state. One explanation for such behavior is that regulators take actions to maximize political support. This paper tests this jurisdictional model using Toxics Release Inventory (TRI) data from 1987 to 1996. We find that facilities' emissions into the air and water are systematically higher in counties that border other states. These results are consistent with the hypothesis that jurisdictional considerations are an important determinant of pollution incidence
Keywords: 330; Industrielle Umweltbelastung; Umweltrecht; Externer Effekt; USA; Gebietskörperschaft